Penerimaan Ubi Jalar Ungu Sebagai Makanan Tambahan Pada Ibu Hamil Berisiko Kekurangan Energi Kronik - Indah Widya Sari; Andi Kasrida Dahlan; Andi Mayanti (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2025)
Chronic Energy Deficiency (CED) in pregnancy threatens maternal and fetal health. Nutrient-dense local foods such as purple sweet potato may support CED prevention. This mixed-methods study explored pregnant women’s perceptions and acceptability of purple sweet potato as a supplementary food and assessed changes in mid-upper arm circumference (MUAC). Three pregnant women at risk of CED participated. Prior to the intervention, purple sweet potato was prepared into porridge, sponge cake, and pudding, followed by interviews to elicit perceptions and preferences. Participants then consumed purple sweet potato daily for one month. Mean MUAC increased from <23.5 cm at baseline to >23.5 cm after the intervention, and all preparations were well accepted. The MUAC improvement may relate to the food’s nutrient contribution, including carbohydrates, protein, iron, and vitamin C. Purple sweet potato shows potential as a locally sourced supplementary food to help prevent CED in pregnant women; however, larger studies with longer follow-up are needed to confirm effectiveness.